Early COVID-19 and protection from Omicron in a highly vaccinated population in Ontario, Canada: a matched prospective cohort study - Altynay Shigayeva; Christopher Kandel; Lubna Farooqi; Zoe Zhong; Anne-Claude Gingras; Brenda L. Coleman; Lois Gilbert; Wayne L. Gold; Maria Major; Tony Mazzulli; Samira Mubareka; Jelena Vojicic; et al. (BMC Infectious Diseases)
Abstract Objectives Predictions regarding the on-going burden of SARS-CoV-2, and vaccine recommendations, require an understanding of infection-associated immune protection. We assessed whether early COVID-19 provided protection against Omicron infection. Methods We enrolled a cohort of adults in Ontario, Canada, with COVID-19 prior to October 2020 (early infection, EI), and a matched cohort with COVID-19 testing and a negative PCR (non-EI). Participants completed baseline surveys then surveys every two weeks until January 2023. Multivariable Cox regression was used to assess factors associated with COVID-19 infection during the first 14 months of Omicron. Results Overall, 624 EI (70%) and 175 (77%) non-EI participants met criteria for analysis; 590 (95%) EI and 164 (94%) non-EI had received at least 2 COVID-19 vaccine doses prior to Omicron. Of 624 EI, 175 (28%) had one SARS-CoV-2 re-infection and 8 (1.3%) had two, compared to 84 (48%) non-EI participants with one, 5 (2.9%) with two and 1 (0.6%) with 3 infections (P < 0.0001). In multivariable analysis of risk factors for Omicron infection, the overall hazard ratio (HR, 95%CI) associated with EI was 0.56 (0.43–0.74); HRs for BA.1/2, BA.4/5 and mixed BA.5/BQ.1/XBB periods were 0.66 (0.45–0.97), 0.44 (0.28–0.68) and 0.71 (0.32–1.56). EI and BA.1/2 infection combined reduced later Omicron infection (HR 0.07 (0.03–0.21) compared to no prior infection. Older age, non-White ethnicity, no children in household, and lower neighbourhood income were associated with reduced risk of infection. Conclusions In our highly vaccinated population, early SARS-CoV-2 infection was associated with a 44% reduction in symptomatic COVID-19 during the first 14 months of Omicron, providing significant protection against re-infection for more than 2 years.